Predicting Lexical Priming Effects from Distributional Semantic Similarities: A Replication with Extension - Günther, Fritz; Dudschig, Carolin; Kaup, Barbara (Frontiers in Psychology, 2016)
In two experiments, we attempted to replicate findings by Günther, Dudschig & Kaup (2016) that word similarity measures obtained from distributional semantics models - Latent Semantic Analysis (LSA) and Hyperspace Analogue to Language (HAL) - predict lexical priming effects. To this end, we used the pseudo-random method to generate item material while systematically controlling for word similarities introduced by Günther et al., which was based on LSA cosine similarities (Experiment 1) and HAL cosine similarities (Experiment 2). Contrary to the original study, we used semantic spaces created from far larger corpora, and implemented several additional methodological improvements. In Experiment 1, we only found a significant effect of HAL cosines on lexical decision times, while we found significant effects for both LSA and HAL cosines in Experiment 2. As further supported by an analysis of the pooled data from both experiments, this indicates that HAL cosines are a better predictor of priming effects than LSA cosines. Taken together, the results replicate the finding that priming effects can be predicted from distributional semantic similarity measures.